2019
DOI: 10.5114/hpc.2019.81106
|View full text |Cite
|
Sign up to set email alerts
|

The use of anti- C6VlsE in the assessment of the effectivness of Lyme disease treatment – a preliminary report

Abstract: Authors' contribution Wkład autorów: A. Study design/planning zaplanowanie badań B. Data collection/entry zebranie danych C. Data analysis/statistics dane-analiza i statystyki D. Data interpretation interpretacja danych E. Preparation of manuscript przygotowanie artykułu F. literature analysis/search wyszukiwanie i analiza literatury G. Funds collection zebranie funduszy Summary Background. The aim of this study was to evaluate the dynamics of changes in IgG anti-C6VlsE concentration in patients treated for ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The moment of tick attachment to the skin is not always noticed and therefore cannot be a decisive criterion for assessment of the risk of the disease. Studies conducted by Shkilna et al [26] have shown that 70% of patients with clinical symptoms of Lyme borreliosis and current anti-Borreliella antibodies declared the occurrence of tick bites (single bites -35%, double bites [27]. In the group of patients with Lyme borreliosis symptoms qualified for antibiotic therapy, 20% did not notice a tick attached to their skin.…”
Section: Discussionmentioning
confidence: 98%
“…The moment of tick attachment to the skin is not always noticed and therefore cannot be a decisive criterion for assessment of the risk of the disease. Studies conducted by Shkilna et al [26] have shown that 70% of patients with clinical symptoms of Lyme borreliosis and current anti-Borreliella antibodies declared the occurrence of tick bites (single bites -35%, double bites [27]. In the group of patients with Lyme borreliosis symptoms qualified for antibiotic therapy, 20% did not notice a tick attached to their skin.…”
Section: Discussionmentioning
confidence: 98%